2022
DOI: 10.3390/children9020240
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health, Bullying, and Victimization among Chinese Adolescents

Abstract: The purpose of this study was to examine if adolescents who experience anxiety or depression have higher levels of reported bullying victimization or perpetration than those who do not. Based on the existing research, we hypothesized that those who experienced moderate or severe depression and anxiety would have higher rates of bullying victimization and perpetration when compared to those who experienced mild or no depression. This study used an observational design, and data were collected from a convenience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
3
6
0
Order By: Relevance
“…These findings align with meta-analysis studies showing that bullied adolescents have a 2.77 times higher risk of experiencing depression than those who are not [33]. Another study on adolescents in China showed that experience of inbully positively correlated with anxiety and depression: The severity of anxiety and depression that adolescents experience depends on how frequently they get bullied [34]. Additionally, a study conducted in Bukittinggi City, West Sumatra, showed that adolescents who experienced bullying are 3.445 times more likely to experience depression than those who have never experienced bullying [35].…”
Section: Discussionsupporting
confidence: 81%
“…These findings align with meta-analysis studies showing that bullied adolescents have a 2.77 times higher risk of experiencing depression than those who are not [33]. Another study on adolescents in China showed that experience of inbully positively correlated with anxiety and depression: The severity of anxiety and depression that adolescents experience depends on how frequently they get bullied [34]. Additionally, a study conducted in Bukittinggi City, West Sumatra, showed that adolescents who experienced bullying are 3.445 times more likely to experience depression than those who have never experienced bullying [35].…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, it is important to understand how the bullying situation is related to young people’s compliance or non-compliance with physical activity recommendations and sedentary behaviour [ 68 ]. Similarly, these findings can be supported by the results of [ 69 ] where it is highlighted that young people who reported that they had bullied others or had been bullied were associated with less sport practices. However, students who reported more sporting activity contributed significantly to predicting that this type of activity decreased bullying levels among adolescents [ 70 ].…”
Section: Discussionsupporting
confidence: 68%
“…In measuring adolescent bullying perpetration, the present study used the bullying subscale of the Chinese version of the Illinois Bully Scale (IBS) [ 71 , 72 ], which has been shown to have good reliability [ 24 , 73 ]. The subscale includes nine items to assess bullying behaviors in the past 30 days.…”
Section: Methodsmentioning
confidence: 99%